1992
DOI: 10.1111/j.1365-2249.1992.tb06881.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of activated γδ T cell receptor bearing T lymphocytes in patients with autoimmune chronic liver disease

Abstract: SUMMARYTo study the possible role of T cells bearing the y6 T cell receptor (TCR) heterodimer in the pathogenesis of autoimmune chronic active hepatitis (AI-CAH) and primary sclerosing cholangitis (PSC) in children, we measured levels of 7^+ T cells in the peripheral blood, assessed the proportion of cells bearing the disulphide-linked (BB3+) and non-disulphide-linked (A13+) subtypes of the receptor, and studied the co-expression of TCR-7(5 and the activation markers HLA-DR and IL-2 receptor (IL-2R), and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…cdT cells have been reported to play an important effector role in the defense against pathogens, tumors and autoimmune diseases [18]; however, these cells have also been suggested to be involved in the pathogenesis of autoimmunity as effector cells [14,[22][23][24][25]. In the present study, we observed the accumulation of cdT cells in liver tissues from AIH patients, which is consistent with a report that peripheral cdT cells were more numerous in AIH patients compared with control subjects [14].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…cdT cells have been reported to play an important effector role in the defense against pathogens, tumors and autoimmune diseases [18]; however, these cells have also been suggested to be involved in the pathogenesis of autoimmunity as effector cells [14,[22][23][24][25]. In the present study, we observed the accumulation of cdT cells in liver tissues from AIH patients, which is consistent with a report that peripheral cdT cells were more numerous in AIH patients compared with control subjects [14].…”
Section: Discussionsupporting
confidence: 94%
“…Recently, the capacity of cdT cells to produce IL-17, a cytokine that can be involved in autoimmune disorders [19], has been established, and the role of IL-17-producing cdT cells has been evaluated in animal models of autoimmune diseases [20,21]. Moreover, several lines of evidence indicate increased numbers of cdT cells in patients with autoimmune disorders, such as multiple sclerosis [22], Behçet's disease [23], Takayasu arteritis [24], and AIH [14,25], suggesting the involvement of cdT cells in the pathogenesis of autoimmune diseases. However, an association between iNKT cells and cdT cells in the context of autoimmune disorders has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Innate and adaptive systems involved [238] Treg defects implicated but disputed [249,252] Lack of Tregs associated with spontaneous fatal autoimmune hepatitis in mouse model [250] NKT cells have inhibitory and stimulatory actions affected by lipid antigens [257,259] Th1, Th2, Th17 lymphocytes key effectors [238] cd T cells increased in blood and liver [300,301] Identified defects may be correctable by medications, molecular agonists or antagonists, or adoptive cell transfer [238] Recognition of cytopathic mechanisms…”
Section: Insights Into Molecular Mimicry As a Basis For Autoimmunitymentioning
confidence: 98%
“…They can also recognize specific antigens presented by class I MHC molecules and secrete the pro-inflammatory cytokines, IL-17 and IFN-c, as part of the adaptive immune response [295,298,299]. Gamma delta (cd) T cells are present in higher concentrations in the peripheral blood [300] and liver tissue [301] of patients with autoimmune hepatitis than in control subjects, and these cells may emerge as indices of disease activity or as additional components of a flawed homeostatic network that cannot adequately modulate the immune response.…”
Section: Gamma Delta (Cd) T Lymphocytesmentioning
confidence: 99%
“…[23][24][25][26][27] IL-4 is a glycosylated, type-I cytokine primarily produced by T cells, natural killer T cells, mast cells and eosinophils. IL-4 initiates signal transduction through either the type I or type II receptor.…”
Section: Introductionmentioning
confidence: 99%